Are Pattern Recognition Receptors Associated with Hepatocellular Carcinoma? - Dertli, Ramazan; Asil, Mehmet; Bıyık, Murat; Karakarcayıldız, Ahmet; Keskin, Muharrem; Kayar, Yusuf; Başdemirci, Müşerref; Ataseven, Hüseyin (Turkish Journal of Gastroenterology, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the important causes of mortality due to malignancy. Toll-like receptors(TLRs) are very important in liver pathophysiology in terms of their roles in the innate immune system, such as the regulation ofinflammation, wound healing, stimulation of adaptive immune responses, promotion of epithelial regeneration, and carcinogenesis.In this study, we planned to examine the role of TLR1 (rs4833095, rs5743551) and nucleotide-binding oligomerization domain(NOD2) (rs2066844, rs2066845, rs2066847) polymorphisms in the development of HCC and their effects on the clinical presentationof HCC patients.Methods: Our study was designed prospectively. Cirrhotic and HCC patients who were followed up in our clinic between January 2015 andSeptember 2018 were included in the study. Sex, age, cirrhosis etiology, Child–Pugh class, and MELD scores were recorded. TLR1 andNOD2 polymorphisms were studied by the PCR method.Results: HCC developed in 88 (31.4%) of the 280 patients who were followed up, either during the recruitment phase of our studyor during the follow-up. The mean follow-up time of our patient group was 17.04 ± 11.72 months, and the mean follow-up time ofHCC patients was 12.09 ± 10.26 months. TLR1 (rs5743551) polymorphism was associated with HCC development (P = .003). TLR1(rs5743551) and NOD2 (rs2066844) polymorphisms were associated with the development of spontaneous bacterial peritonitis (SBP)in the HCC patient group (P = .013 and P = .021, respectively).Conclusion: We think that increased bacterial translocation in cirrhotic patients may contribute to HCC development by causing chronicinflammation, especially in patients with TLR 1 (rs5743551) polymorphism.